Rosuvastatin microcirculatory effects in patients with dyslipidemia and arterial hypertension - D. V. Nebieridze; G. R. Kulieva; V. A. Vygodin (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To assess microcirculation (MC) dynamics during rosuvastatin therapy in patients with dyslipidemia (DL) and mild to moderate arterial hypertension (AH). Material and methods. The study included 25 patients with total cholesterol (TCH) level >5,0 mmol/l, low-density lipoprotein CH (LDL-CH) level > 3,0 mmol/l, systolic blood pressure (SBP) 140-179 mm Hg, and diastolic BP (DBP) 90-109 mm Hg. For 12 weeks, all participants received rosuvastatin, in constant dose of 10 mg/d. MC was assessed by laser Doppler flowmetry. Results. Rosuvastatin beneficially influenced MC, in various pathological MC types – spastic and hyperemic, according to main MC parameters – MC and capillary blood flow reserve. Regulatory mechanisms’ changes (myogenic amplitude increase) pointed to a decrease in peripheral vascular resistance. Another positive vascular effect of rosuvastatin manifested in significant SBP and DBP reduction, by 8 and 6 mm Hg, respectively. Rosuvastain also demonstrated a substantial lipid-lowering effect. Conclusion. A new statin, rosuvastatin, demonstrated not only substantial lipid-lowering effect, but also beneficial vascular action: it improved MC and reduced BP in patients with DL and mild to moderate AH.